Actor Collaboration in Implementing Stunting Handling Policy in Landak District - Kusnadi, Dedi; Nge, Herri Junius (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to find out and analyze the collaboration of actors in the implementation of stunting handling policies in Landak Regency. This research was conducted with qualitative methods, with the type of descriptive research. The results of the study indicate that the collaboration of actors in the implementation of stunting handling policies in Landak Regency has not run effectively, there was still sectoral ego and there is no willingness by the authorities and interested parties to cooperate with each other in handling stunting problems. Actors involved in handling stunting still seem to give the responsibility for handling stunting to the Health Office, while other agencies tend to be passive, while it is known that the problem of stunting is not only related to nutrition, but also relates to the behavior and awareness of the village community towards a healthy lifestyle, especially in rural areas. with high stunting rates. So far, the handling of stunting by related parties has been echoed more at the bureaucratic level, but has not been conveyed conceptually and operationally in the field, especially with the village government and village communities, so that village officials have not been able to actively participate in it. The community in collaboration is still positioned as an object and not a subject, so that the community still has a strong dependence on directives, instructions or socialization from the government.